A Metallic Ion‐Induced Self‐Assembly Enabling Nanowire‐Based Aerogels (Small 44/2021). Issue 44 (4th November 2021) - Shang, Qi‐Guo; Wang, Kang; Li, Lin‐Ge; He, Zhen; Jiang, Hui‐Jun; Zhu, Jian‐Hua; Liu, Jian‐Wei
Abstract : Nanowire Aerogels In article number 2103406, Zhen He, Hui‐Jun Jiang, Jian‐Wei Liu, and co‐authors present a hydrothermal process for macroscopic 3D aerogels induced by metallic ion coordination, which pave new opportunities for other material systems. The assembly mechanism, that the metallic ions induced dynamic behavior of nanowires, is revealed via molecular dynamics theoretical evaluation.